2002
DOI: 10.1080/13642810210146443
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of superconductivity and ferromagnetism in the graphite-sulphur system

Abstract: Superconducting characteristics such as the Meissner-Ochsenfeld state, screening supercurrents and hysteresis loops of type-II superconductors were observed from the temperature and magnetic field dependences of the magnetic moment, m(T, H), in graphite powders reacted with sulfur for temperatures below 9.0 K. The temperature dependence of the lower critical field H c1 (T) was determined and the zero-temperature penetration depth, λ(0), was estimated (λ(0) = 2270 Å). The superconductivity was observed to be hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
49
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 19 publications
4
49
0
Order By: Relevance
“…In particular, it has been demonstrated that the SC of graphite-sulfur (C-S) composites occurring within some sort of "grains" or domains [5,2] is highly anisotropic and associated with the graphite planes [2]. The SC domains coexist with the FM of pure graphite [1], and a continuous crossover from SC to FM-like behavior could be achieved increasing either the applied magnetic field H or the temperature T.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, it has been demonstrated that the SC of graphite-sulfur (C-S) composites occurring within some sort of "grains" or domains [5,2] is highly anisotropic and associated with the graphite planes [2]. The SC domains coexist with the FM of pure graphite [1], and a continuous crossover from SC to FM-like behavior could be achieved increasing either the applied magnetic field H or the temperature T.…”
mentioning
confidence: 99%
“…The superconducting state coexists with the ferromagnetism of pure graphite, and a continuous crossover from superconducting to ferromagnetic-like behavior could be achieved by increasing the magnetic field or the temperature. The angular dependence of the magnetic moment m(α) provides evidence for an interaction between the ferromagnetic and the superconducting order parameters.An interplay between ferromagnetic (FM) and superconducting (SC) behavior of graphite and related systems has recently been observed [1,2] and theoretically analyzed [3,4]. In particular, it has been demonstrated that the SC of graphite-sulfur (C-S) composites occurring within some sort of "grains" or domains [5,2] is highly anisotropic and associated with the graphite planes [2].…”
mentioning
confidence: 99%
See 3 more Smart Citations